AN INNOVATIVE PEDAGOGICAL SIMULATION AND ANIMATION OF A SHOVEL-TRUCK SYSTEM (Nigerian Journal of Technology, 2023)
This paper  aims to simulate and animate a shovel-truck system in an open pit mine using Arena® Software for teaching and learning purposes. The shovel-truck system is the use of loading and dumping units in the transportation of materials. The shovel-truck system has wide application in open pit mining. Animation of a shovel-truck system in Arena® is a reflection of the logic defined by the module’s flowcharts. Arena® software is a widely used simulation software based on Discrete Events. The data were analysed by an input analyser tool in Arena® software to get distributions and expressions for the shovel-truck system. The shovel-truck system was then modelled in the software. The developed animated model depicts the exact activities in open pit mines.